Social media for cultural communication: A critical investigation of museums' Instagram practices - Dimitrios Amanatidis; Ifigeneia Mylona; Spyridon Mamalis; Irene (Eirini) Kamenidou (Journal of Tourism, Heritage & Services Marketing, 2020)
Purpose: The purpose of the study is to investigate the use of Instagram by museums in the Greek cultural scene. Specifically, the study focuses on examining the use of Instagram by museum communication professionals and aims at carrying out a twofold investigation: Firstly, if and how the Instagram is used to reach out to their visitors and secondly, the public response to this type of communication. Methods: A list of all archaeological museums in Greece was obtained and related Instagram accounts were retrieved. The dataset structure was enhanced by eleven variables, which were measured and visualized by a descriptive statistics analysis. Inter-variable correlations, normality and equality tests were also performed. Moreover, a linear predictive model for the number of museum tags was investigated. Results: Only one museum in Greece maintains an Instagram account. Visitors usually tag museum exhibits or people and exhibits on the photographs they upload on their personal accounts. T-tests and Mann-Whitney U tests revealed equal distributions for all variables between central and peripheral museums. Implications:Museum officials have not seized the opportunity offered by social media and especially Instagram today. Their importance seems to be underestimated. With respect to the linear model derived, results suggest that more features should be surveyed; this could be the subject of future research studies.
Keywords: N7; L82; D83; 330; social media; communication; digital marketing; Instagram; multiple regression